2009
DOI: 10.1016/j.bbmt.2009.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Race and Socioeconomic Status Influence Outcomes of Unrelated Donor Hematopoietic Cell Transplantation

Abstract: Success of hematopoietic-cell transplantation (HCT) can vary by race, but the impact of socioeconomic-status (SES) is not known. To evaluate the role of race and SES, we studied 6207 unrelated-donor myeloablative HCT recipients transplanted between 1995–2004 for acute or chronic leukemia or myelodysplastic syndrome. Patients were reported by transplant center to be White (n=5253), African-American (n=368), Asian/Pacific-Islander (n=141), or Hispanic (n=445). Patient income was estimated from residential ZIP Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
155
4
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(174 citation statements)
references
References 50 publications
12
155
4
2
Order By: Relevance
“…Although the percentage of African Americans among other ethnic groups varied significantly among recent transplant studies, 23,31 this number is comparable to the larger CIBMTR studies 22,30 as well as to past leukemia studies 13,14 and indicative of our current leukemia/hematologic malignancy population. Despite this, we acknowledge that the absolute number of African Americans in this study is small, and, given this, the study may lack the power to detect significant racial differences.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Although the percentage of African Americans among other ethnic groups varied significantly among recent transplant studies, 23,31 this number is comparable to the larger CIBMTR studies 22,30 as well as to past leukemia studies 13,14 and indicative of our current leukemia/hematologic malignancy population. Despite this, we acknowledge that the absolute number of African Americans in this study is small, and, given this, the study may lack the power to detect significant racial differences.…”
Section: Discussionmentioning
confidence: 59%
“…In contrast to the previous study, however, socioeconomic status in and of itself was found to be associated with worse unrelated donor HCT outcomes independent of race. 22 Another more recent study from the CIBMTR 31 also reported worse survival outcomes, attributed to more severe acute GvHD, among African Americans (29%) compared with whites (13%) undergoing HCT for aplastic anemia. In contrast, another large registry study demonstrated a difference in survival rates in Hispanics, but not in African Americans, compared with whites after allogeneic HCT for AML, ALL and CML.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of AML is prolonged, expensive, and complex. It is conceivable that patients who are not married and have a low income have a more fragile support network with which to cope with the physical, material, and emotional challenges of AML treatment, thereby affecting access to and outcomes of postremission therapy (including HSCT) 31,32 and the treatment of recurrent disease. Yet another possibility is that patients with unfavorable NBFs also have more serious comorbidities affecting their opportunity to benefit from aggressive therapy.…”
Section: Discussionmentioning
confidence: 99%